Knowledge Level of Improved Buffalo Husbandry Practices in Peri-urban areas of Surat city of Gujarat - Sabapara, Ghanshyam Prabhulal (Indian Journal of Animal Production and Management, 2024)
A field survey was conducted in the Peri-urban areas of Surat city of Gujarat to assess the knowledge level of randomly selected 50 buffalo farm owners about improved buffalo husbandry practices. The analysis of data collected by personal interview method revealed that majority of buffalo owners had medium knowledge level on different aspects of improved buffalo husbandry practices viz. 76% for feeding, 56% for breeding, 72% for general management and 50% for health care. The overall knowledge levels of the respondents in improved buffalo husbandry practices fall under low, medium and high categories are 16%, 68% and 16%, respectively. The knowledge index of different aspect of improved buffalo husbandry practices of feeding, breeding, general management and health care were 42.50, 67.575, 45.50 and 54.25%, respectively and overall knowledge index of improved buffalo husbandry practices was 52.50 % in the study area.